Utilization of Solid Waste PT Semen Bosowa as Zeolite for Industrial Waste Water in South Sulawesi. Issue 1 (1st December 2022) - Abdullah, N O; Safruddim,; Tumpu, M
Abstract: One of the major industries in Eastern Indonesia engaged in manufacturing is PT Semen Bosowa. In the process of processing cement raw materials there are several stages, one of the stages in the process is the mixing process that occurs in the Raw Grinding Mill section. In addition to grinding or smoothing the cement raw material, it also serves as a material dryer. Some residual material is wasted during the process as solid waste and cannot be processed again so that it will have an impact on the environment. so it needs further handling so as not to cause environmental problems. One of the efforts that can be made is to utilize solid waste material as a zeolite replacement adsorbent. The material has a composition similar to zeolite. This study aims to determine the effect of PT Semen Bosowa solid waste as a zeolite substitute on reducing the TDS, BOD, and COD values of industrial wastewater. The method used in the research, namely the wastewater sample is put into the reservoir (tub I), then flowed continuously into tub II which is filled with solid waste material as zeolite. The sampling technique is carried out after the wastewater flows from tub II then collected in a storage container and ready to be analyzed for TDS, BOD, and COD parameters of wastewater. The amount of TDS, BOD and COD reduction from PT Semen Bosowa laboratory wastewater after going through zeolite adsorbent was 3.79%, 58.33%, and 58.35%, respectively.